2013
DOI: 10.1007/s00405-013-2476-2
|View full text |Cite
|
Sign up to set email alerts
|

From laryngeal epithelial precursor lesions to squamous carcinoma of the larynx: the role of cell cycle proteins and β-catenin

Abstract: Novel markers to accurately predict the risk of malignant transformation in laryngeal epithelial precursor lesions (EPL) are needed. We tried to identify some molecular alterations occurring in laryngeal tumorigenesis. In this study, 60 paraffin-embedded EPL and 17 metachronous invasive carcinomas were immunostained for markers associated with proliferation (Ki67), cell cycle control (p53, p21, p16, p27, cyclin D1), and cell adhesion and invasion (laminin and β-catenin). Aberrant expression of p16 and p53 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 29 publications
1
29
0
Order By: Relevance
“…After excluding studies not meeting the inclusion criteria, nine articles were finally entered in the review for qualitative evaluation and quantitative meta-analysis. 24,25,[29][30][31][42][43][44][45] 3.2 | Study characteristics Table 1 summarizes the characteristics of the nine studies selected, which reported on a total of 496 patients with malignant transformation of head and neck PMDs; sample sizes ranged between 28 and 90 patients. Cyclin D1 overexpression was addressed by seven studies and CCND1 amplification by two.…”
Section: Results Of the Literature Searchmentioning
confidence: 99%
See 4 more Smart Citations
“…After excluding studies not meeting the inclusion criteria, nine articles were finally entered in the review for qualitative evaluation and quantitative meta-analysis. 24,25,[29][30][31][42][43][44][45] 3.2 | Study characteristics Table 1 summarizes the characteristics of the nine studies selected, which reported on a total of 496 patients with malignant transformation of head and neck PMDs; sample sizes ranged between 28 and 90 patients. Cyclin D1 overexpression was addressed by seven studies and CCND1 amplification by two.…”
Section: Results Of the Literature Searchmentioning
confidence: 99%
“…When RR data were not reported, odds ratios (ORs) were extracted as an approximation of this measure . In order to facilitate the interpretation of results, we performed sensitivity analyses in which the meta‐analysis was repeated, first omitting studies calculating RRs, and then those calculating ORs …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations